Relação de parentesco de uma população isolada de toninha (Pontoporia blainvillei, Gervais & D’orbigny, 1844) no Brasil, Sudoeste do Oceano Atlântico - Oliveira, Vanessa Kuboyama Marques de (2023)
The high mobility of cetaceans can make difficult to determine the area of occupation of one or more populations of a species. The species Pontoporia blainvillei, known as toninha or franciscana, is endemic to the southwest Atlantic Ocean, occurring from Itaúnas, in Espírito Santo, Brazil, to the province of Chubut, in Argentina. The northern part of its range is not continuous. Genetic studies have demonstrated that the Espírito Santo population is geographically isolated and genetically different from others recognized throughout the distribution. Studies involving kinship can provide us data on the degree of relationships, mating system and endogamy of populations. Thus, this study aimed to evaluate the social structure of franciscana dolphins, as well as their current genetic diversity on the coast of Espírito Santo, Brazil. For this, the mitochondrial DNA (D-loop region) of 95 individuals found stranded on beaches from 2005 to 2023 was amplified. The amplified fragments (342bp) from 80 individuals showed us three haplotypes. A single population with low diversity was found, with haplotypic diversity of 0.026 and nucleotide diversity of 0.025. The nuclear DNA of 82 individuals showed the lowest diversity when compared to franciscana dolphins from other occurrence areas, with the expected heterozygosity being 0.605 and observed 0.473 and also did not reject the hypothesis of just one population, with a low effective population size (Ne = 60.2). Of the 81 individuals genotyped for kinship relationships, 80 showed some type of relationship, whether first or second degree. Inbreeding and a greater number of first-degree relationships were detected in the population. This species is considered critically endangered and has been highly impacted by accidental captures and habitat degradation. Considering factors such as small population size, low genetic diversity, absence of gene flow and presence of inbreeding, factors considered an extinction vortex, the need for different conservation actions focused on reducing accidental captures of this species in the Espírito Santo region and improving the quality of the environment where this species lives.